The Use of Teaching Aids in Increasing Student Motivation at Elementary School - Haddar, Gamar Al; Azmi, Nurul (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
This study aims to determine the role of teaching aids by teachers in increasing student motivation at Elementary School 027 Samarinda Ulu in the 2019/2020 learning year. The technique of determining the subject used in this research was purposive sampling, and the data analysis techniques used data collection, data selection, data presentation, and conclusion drawing. The type of triangulation used is source triangulation.The result of the research is that the teacher uses teaching aids that are two-dimensional and three-dimensional. The increase in learning motivation for grade 1B students is good, and this is evidenced by the willingness of students to bring props, increasing the enthusiasm of students to improve their lack of grades, increasing the focus of student learning, the enthusiasm of students in demonstrating the use of teaching aids directly.